Estimasi Biomassa dan Karbon Tegakan Rhizophora apiculata Hasil Aforestasi di Kecamatan Mawasangka - La Ode Abdul Fajar Hasidu; Maharani Maharani; Indra Ardiansyah; Syahrul Muhammad; Salsa Mariska (Journal of Marine Research, 2026)
Rhizophora apiculata is a mangrove species commonly used in revegetation programs because its propagules are easy to obtain, and its growth is relatively easy to control. R. apiculata also has great potential in storing carbon, so it is important to know its contribution to carbon stocks in coastal areas. This study aims to determine the density, estimate biomass, and carbon stocks of R. apiculata from community revegetation on the coast of Mawasangka District, Central Buton Regency. The study was conducted in October-November 2025. Vegetation data collection used a 50-meter quadratic transect method perpendicular to the coastline, with two transect lines and six plots 100 m². The percentage of canopy cover was measured using the Hemispherical Photography method. Biomass and carbon stock estimation used the Google Earth Engine approach and direct measurements using the Allometric model. The results showed that the percentage of canopy cover of R. apiculata was 74.10 ± 14.53%, which is included in the good/dense category. Based on the dbh size, the highest density was in the 4–6.99 cm and 7–9.99 cm size classes with values of 2616.66 ind/ha2 and 1666.66 ind/ha2, respectively. The total biomass was 115.97 tons/ha2, consisting of AGB 111.81 tons/ha2 and BGB 4.15 tons/ha2. This value is directly proportional to the total carbon stock of 54.50 tons C/ha2 (AGC: 52.55 tons C/ha2; BGBC: 1.95 tons C/ha2). In general, the biomass and carbon stock values in the upper part of the stand were higher than those in the lower part. R. apiculata resulting from revegetation is still in the early stages of growth with a relatively small dbh size. Nevertheless, its potential as a carbon store is quite good. Efforts to preserve and expand the revegetation area need to be continued to increase the potential for carbon absorption in coastal areas.